Peran Intermediasi Sosial Perbankan Syariah bagi Masyarakat Miskin - Syafii Antonio; Hilman F. Nugraha (TSAQAFAH, 2013)
The ongoing  Islamic banking gets a lot of criticisms due to its unability to become the manifestation of the Islamic values which can be utilized by all people. These criticisms can be attributed to at least some indicators such as the dominance of non profit sharing contract (Murabahah) on Islamic banking practices that can only be enjoyed by the middle to upper class of  society, or the lack of optimization of the innovative Islamic banking products that can touch the majority of  the poor. This paper would like to discuss and explore the possible role of  social intermediation that can be carried out by the Islamic banking in addition to its role of  financial intermediation. By doing so, it can answer the stigma which states that Islamic banking is not pro poor. Based on the literature review and discussion, the role of  social intermediation by using social funds which are accordance to the perspective of  Islam namely charity, infaq, Sadaqah, endowments, and grants (ZISWAH) can be applied as the additional products or policies of  Islamic banking in order to serve the poor through several strategies, namely: (1) the establishment of special units for social intermediation and (2) the cooperation with LKMS in certain programs special for the poor.